The identification and assessment of potential hazards from suspected contamination posed by disused industrial sites - Fischer, Bernhard (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
In order to facilitate initial risk assessment on a large number of sites, a system of assessment was tested which concentrates solely on the key factors, such as sources of contamination, the carritage of harmful substances into the ground water and effects on human beings. The factors were subdivided into gradable groups or classes according to scientific criteria, thus establishing a system and a rule for computation. Determinants proved to be both the scale of investigation and the availability of data. The numerical score provides a (limited) basis for comparing and classifiying the differing degrees of hazard posed by a large number of sites.